Etika Dan Tanggung Jawab Remaja Dalam Penggunaan Media Sosial - Aulia Masruroh; Nur Indah Sari; Eka Septiyani (Indo Publishing, 2025)
The development of information and communication technology has brought major changes in various aspects of life, including how to communicate and socialize. One real manifestation of this change is the presence of social media that allows every individual to interact instantly without the limits of space and time. The various platforms such as facebook, Instagram, twitter and tiktok have become places for billions of people to share information, express themselves and build social networks. This activity aims to increase participants awareness of the importance of being wise in using social media, including in terms of ethics, security and responsibility. The method used was a face to face seminar held at SMAN 36 Jakrta, with a participatory approach in the form of material delivery, discussion and direct practice. The target of the activity is 36 students aged between 16 – 18 years with the indicator of success being an increase in students knowledge about ethics and the responsibilities of teenagers in using social media. The results of the activity showed that participant were able to understand the ethics and responsibilities of social media and were actively involved in discussions and questions and answers. The awareness of ethics and responsibility in social media has increased according to questionnaire evaluation. The activity makes a positive contribution in forming responsible digital behavior among teenagers.